Clinical trials in transcatheter aortic valve replacement. (July 2016) - Barker, Colin M.
Abstract : Purpose of review: Clinical trials in transcatheter aortic valve replacement (TAVR) have been essential in establishing the effectiveness as well as the limitations of this exciting and disruptive technology. This review will focus on clinical trials related to TAVR that have been presented in the past year or are currently enrolling, as well as future trials that are in the planning stages. Recent findings: The currently available devices have gone through iterations to improve safety and outcomes, including lower profiles to reduce bleeding complications as well as adding a sealing skirt or allowing for re-positioning in order to decrease para-valvular regurgitation and need for a permanent pacemaker. The intermediate-risk clinical trials will be finishing soon and will be followed by low-risk trials. Ancillary devices will likely continue to expand the access to this therapy. One of the main challenges moving forward will be the post-TAVR pharmacotherapy. Summary: Recently, improvements in first-generation devices have led to improved outcomes. Current trials evaluating novel TAVR platforms and lower risk patients as well as ancillary devices will likely continue to expand the access to this therapy.